IMPLEMENTATION OF THE KAMPUNGE AREK SUROBOYO RAMAH PEREMPUAN DAN ANAK KAMPUNG BELAJAR PROGRAM - Theofani, Gabriela Zera; Nawangsari, Ertien Rining (Jurnal Governansi, 2025)
Challenges in accessing education remain a significant obstacle, especially in urban areas such as Surabaya City, which has the lowest School Participation Rate (SPR) in East Java for the 7-12 age group. One of the government's efforts to improve educational access is through the Kampunge Arek Suroboyo Friendly to Women and Children Program (KAS-RPA) under the Learning Village category. This study aims to analyze and describe the implementation of this program in Gebang Putih Village, Sukolilo District, Surabaya City, using the public policy implementation theory that involves four key factors influencing the success or failure of policy implementation: communication, resources, disposition, and bureaucratic structure. The research method is qualitative with a descriptive approach to deeply analyze and describe the program's implementation. The unit of analysis is the KAS-RPA Learning Village Program in Gebang Putih Village, with informants including representatives from DP3APPKB Surabaya City, the Village Head, the Chairperson of RW 01 Gebang Putih Village, the program coordinator, program educators, and families or parents of program participants. Data validity was tested through credibility checks using source triangulation and member checking. The findings show that the implementation of the KAS-RPA Learning Village Program in Gebang Putih Village was relatively successful. This success was measured through direct observation, in-depth interviews with program implementers, documentation, and analysis of primary data collected during the implementation process. The success was driven by effective communication, adequate availability of resources, positive disposition from the implementers, and a clear and flexible organizational structure. However, challenges remain, including limited funding to ensure sustainability and optimization of the program, as well as improving formal documentation to support future program evaluations. This study contributes to understanding the key factors in implementing educational programs that impact the improvement of access and quality of education.